Time to initiation of dialysis and length of stay in hospitalized patients with kidney damage: a cross-sectional study - Douglas Vieira Gemente; Marcelo Rodrigues Bacci (São Paulo Medical Journal)
ABSTRACT BACKGROUND: Universal healthcare is a cornerstone of Brazil’s public health system. However, delayed diagnosis and treatment of chronic kidney disease (CKD) remain substantial issues. The scarcity of outpatient dialysis facilities contributes to extended hospital stays. This study aimed to examine how the time to dialysis initiation (TID) impacts mortality in patients with renal disease. OBJECTIVES: This study aimed to evaluate the correlation between variables affecting TID and mortality in hospitalized patients with renal disease. DESIGN AND SETTING: A cross-sectional study was conducted at Santa Marcelina Hospital in São Paulo. METHODS: This cross-sectional study was conducted in a tertiary hospital, involving adults with kidney disease who were referred to the emergency department between 2014 and 2017. Primary outcomes included TID and mortality rates. RESULTS: Among the 402 patients studied, the average age was 58.6 years, and 59.4% were men. The median hospital stay was 44.5 d. Notably, 28.1% of the patients began dialysis under emergency conditions. Diabetes and hypertension were the most prevalent causes of renal disease. A positive correlation was found between age and TID (P = 0.007). CONCLUSIONS: Primary care in Brazil often fails to effectively detect and manage CKD, leading to a higher incidence of emergency dialysis, particularly among older adults. This delay correlates with increased mortality rates. Older age is associated with delayed TID, prolonged hospital stays, and consequently higher mortality. These findings highlight the need for better primary care to effectively manage CKD and reduce hospitalization and mortality.